Normal Skin Cells Increase Aggressiveness of Cutaneous Melanoma by Promoting Epithelial-to-Mesenchymal Transition via Nodal and Wnt Activity - Gustavo Untiveros (MDPI AG, 2021)
Melanoma is a lethal form of skin cancer triggered by genetic and environmental factors. Excision of early-stage, poorly aggressive melanoma often leads to a successful outcome; however, left undiagnosed these lesions can progress to metastatic disease. This research investigates whether the exposure of poorly aggressive melanoma to certain normal skin cells can explain how non-metastatic melanoma becomes more aggressive while still confined to the skin. To this end, we used a serial co-culture approach to sequentially expose cells from two different, poorly aggressive human melanoma cell lines against normal cells of the skin beginning with normal melanocytes, then epidermal keratinocytes, and finally dermal fibroblasts. Protein extraction of melanoma cells occurred at each step of the co-culture sequence for western blot (WB) analysis. In addition, morphological and functional changes were assessed to detect differences between the serially co-cultured melanoma cells and non-co-cultured cells. Results show that the co-cultured melanoma cells assumed a more mesenchymal morphology and displayed a significant increase in proliferation and invasiveness compared to control or reference cells. WB analysis of protein from the co-cultured melanoma cells showed increased expression of Snail and decreased levels of E-cadherin suggesting that epithelial-to-mesenchymal transition (EMT) is occurring in these co-cultured cells. Additional WB analysis showed increased levels of Nodal protein and signaling and signs of increased Wnt activity in the co-cultured melanoma cells compared to reference cells. These data suggest that interaction between poorly aggressive melanoma cells with normal cells of the skin may regulate the transition from localized, poorly aggressive melanoma to invasive, metastatic disease via Nodal and/or Wnt induced EMT.